Analisis Penerapan Knowledge Management System dengan Task-Technology FIT pada Sekolah Tinggi Manajemen Informatika dan Komputer Parna Raya Manado - Maikel Bolung; Irfan Ramandhani; Elkana Lewi Santoso (POLITEKNIK CAHAYA SURYA, 2020)
A fundamental need now is that knowledge management is actually applied in tertiary institutions, because the ability to manage existing knowledge in tertiary institutions can be the strength needed for the tertiary institution to survive and advance.Knowledge management is an effort to improve and manage knowledge to be more quality for universities. This study analyzes the extent of the application of the Knowledge Management System at the School of Information and Computer Management (STMIK) Parna Raya Manado through its website www.parnaraya.ac.id using the Task-Tecnology Fit method to measure the implementation of a knowledge management system based website at STMIK Parna Raya Manado.Keywords: system, management, knowledge